2021
DOI: 10.1111/gcb.16005
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected high retention of15N‐labeled nitrogen in a tropical legume forest under long‐term nitrogen enrichment

Abstract: The responses of forests to nitrogen (N) deposition largely depend on the fates of deposited N within the ecosystem. Nitrogen‐fixing legume trees widely occur in terrestrial forests, but the fates of deposited N in legume‐dominated forests remain unclear, which limit a global evaluation of N deposition impacts and feedbacks on carbon sequestration. Here, we performed the first ecosystem‐scale 15N labeling experiment in a typical legume‐dominated forest as well as in a nearby non‐legume forest to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 100 publications
1
2
0
Order By: Relevance
“…The fluxes in our study site were comparable to those that were observed in temperate forests at lower altitudes (Geng et al., 2020; Michalzik et al., 2001; Neff & Asner, 2001). Both low and high N addition tended to increase TDN leaching from both organic and mineral soil layers; which is consistent with previous findings (Fang et al., 2009; Magill et al., 2000; Mao et al., 2022; Song et al., 2017, 2019). TDN leaching from the organic layer under high N addition was significantly greater than that under low N addition, supporting the first hypothesis that a higher dosage of N addition had a greater effect on TDN leaching.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The fluxes in our study site were comparable to those that were observed in temperate forests at lower altitudes (Geng et al., 2020; Michalzik et al., 2001; Neff & Asner, 2001). Both low and high N addition tended to increase TDN leaching from both organic and mineral soil layers; which is consistent with previous findings (Fang et al., 2009; Magill et al., 2000; Mao et al., 2022; Song et al., 2017, 2019). TDN leaching from the organic layer under high N addition was significantly greater than that under low N addition, supporting the first hypothesis that a higher dosage of N addition had a greater effect on TDN leaching.…”
Section: Discussionsupporting
confidence: 92%
“…We noted that the method of zero‐tension lysimeters has its limitations in the TDN fluxes calculation. However, this is a relatively simple and highly effective method for collecting soil solution and examining the nutrient losses, as evidenced by its extensive use in many studies (Fang et al., 2009; Mao et al., 2022; McDowell et al., 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, understory vegetation plays an important role in the absorption and cycling of 15 N fertilizers in forest ecosystems (Chang & Preston, 2000). However, there are relatively few measurements of 15 N retention in understory vegetation (Buchmann et al., 1996; Li et al., 2019; Liu, Yu, et al., 2017; Mao et al., 2022; Wang, Chen, et al., 2021), which poses a risk of underestimating 15 N retention in forest ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the 15 N tracer method integrates the isotopic composition of external N inputs, the processes of N transformation, assimilation and loss, as well as the isotopic fractionation during internal migration, aiding in determining the availability of different N forms and the competitive absorption of N by plants and soils (van Cleve & White, 1980). Therefore, the 15 N tracer method has been widely utilized to investigate N retention and allocation in forest ecosystems (Koopmans et al., 1996; Mao et al., 2022; Perakis et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of elevated N deposition on N retention capacity in subtropical and tropical forests were hot topic but still under debates. Soil and plant play dominant roles in retaining added N according to the results of 15 N addition experiment, but the N retention capacity, indicated by 15 N recovery percentage, varies greatly from 16% to 42% in soil and from 6% to 60% in plants among different studies (Gurmesa et al, 2016(Gurmesa et al, , 2021Liu et al, 2017;Mao et al, 2022;Sheng et al, 2014;Wang et al, 2018;Wang, Chen, et al, 2021). The divergent retention capacities of N in soil and plants are mainly associated with N role in providing plant nutrient retention service and is sensitive to atmospheric N deposition.…”
Section: Introductionmentioning
confidence: 99%